From Neighborhoods to Nations : The Economics of Social Interactions - Ioannides, Yannis Menelaos (Book collections on Project MUSE., 2013)
Just as we learn from, influence, and are influenced by others, our social interactions drive economic growth in cities, regions, and nations - determining where households live, how children learn, and what cities and firms produce. "From Neighborhoods to Nations" synthesizes the recent economics of social interactions for anyone seeking to understand the contributions of this important area. Integrating theory and empirics, Yannis Ioannides explores theoretical and empirical tools that economists use to investigate social interactions, and he shows how a familiarity with these tools is essential for interpreting findings. The book makes work in the economics of social interactions accessible to other social scientists, including sociologists, political scientists, and urban planning and policy researchers. Focusing on individual and household location decisions in the presence of interactions, Ioannides shows how research on cities and neighborhoods can explain communities' composition and spatial form, as well as changes in productivity, industrial specialization, urban expansion, and national growth. The author examines how researchers address the challenge of separating personal, social, and cultural forces from economic ones. Ioannides provides a toolkit for the next generation of inquiry, and he argues that quantifying the impact of social interactions in specific contexts is essential for grasping their scope and use in informing policy. Revealing how empirical work on social interactions enriches our understanding of cities as engines of innovation and economic growth, "From Neighborhoods to Nations" carries ramifications throughout the social sciences and beyond.